Crustal structure and the seismogenic environment in Yunnan imaged by double-difference tomography - Sun, Ya; Deng, Shilin; Huang, Jiwen (Frontiers in Earth Science, 2023)
The large-scale faulting and earthquake activities developed extensively in the Yunnan area associated with the collision of India and Eurasia. The fine crustal structure can better understand the crustal deformation, seismogenic environment, and rupture processes. We performed a new 3-dimensional (3-D) P wave velocity structure and seismic relocation using double-difference tomography based on seismic observations. The tomography images show that large-scale low-velocity anomalies spread around the margin of the south Chuandian block Xiaojiang fault (XJF) and the Lijiang-Xiaojinhe fault (LJ-XJHF)) in the middle and lower crust. There is an obvious high-speed anomaly in the Emeishan large igneous province (ELIP). We infer that the low-velocity anomaly under the LJ-XJHF zone may be derived from the lower crustal flow extruded from the central Tibetan plateau and obstructed by the ELIP. While the velocity anomalies around the XJF might be caused by the shear heating associated with the large-deep strike-slip fault and the southeast transmission stress. The inversion results also show that the Yangbi earthquake occurs at the NW-SE boundary of high- and low-velocity from the upper crust to the lower crust, which coincides well with the location of the Yangbi earthquake sequence and the Weixi-Qiaohou fault. Meanwhile, the earthquake relocations show that the aftershocks are mainly distributed at low velocities. All the above research results indicate that the Yangbi earthquake might be attributed to the intrusion of the soft material flow along the Weixi-Qiaohou fault in the NW-SE direction. These low-viscosity crustal materials would cause brittle fractures and result in NW-SE sinistral strike-slip faults.